(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the most honorable creation of God, our master Muhammad, may God’s prayers and peace be upon him, his pure and pure family, his companions, and those who follow them in goodness until the Day of Judgment.And after:In addition to being ministers in the Andalusian state, the poets of Bani al-Qabatrana represented the model of Andalusian poetry in the age of sects. This study included a description of the high rhetorical ability in photography and creativity of these people, and their great influence on nature and the life they lived. It has been shown through poetic examples that they were emanating from real experiences they went through in their lives. In addition, the technical aspect of their poetry was studied through metaphor, analogy and metaphor, and it was found that most of their poetry was easy and clear, with no strangeness or complexity. These poets achieved a remarkable amount of depth in meaning and subtlety in depiction.